2021
DOI: 10.1016/j.ijid.2021.03.093
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid-monoresistant tuberculosis in France: Risk factors, treatment outcomes and adverse events

Abstract: Isoniazid-monoresistant tuberculosis (HR-TB) is the most prevalent form of drug-resistant TB worldwide and in France and is associated with poorer treatment outcomes compared with drugsusceptible TB (DS-TB). The objective of this study was to determine the characteristics of HR-TB patients in France and to compare outcomes and safety of treatment for HR-TB and DS-TB. Methods: We performed a case-control multicenter study to identify risk factors associated with HR-TB and compare treatment outcomes and safety b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…We found a low level of primary resistance to isoniazid and rifampicin detected by drug sensitivity testing on cultures at 3.7% for isoniazid resistance and 0.5% for rifampicin, which was lower than that reported in a recent French study [ 9 ]. For the 3 patients with isoniazid resistance detected at baseline in the PCR arm, treatment was adapted within the first week of treatment.…”
Section: Discussioncontrasting
confidence: 79%
“…We found a low level of primary resistance to isoniazid and rifampicin detected by drug sensitivity testing on cultures at 3.7% for isoniazid resistance and 0.5% for rifampicin, which was lower than that reported in a recent French study [ 9 ]. For the 3 patients with isoniazid resistance detected at baseline in the PCR arm, treatment was adapted within the first week of treatment.…”
Section: Discussioncontrasting
confidence: 79%
“…Additionally, Dean et al reported a prevalence that ranged from 10.7% to 27.2% from aggregated DR-TB data reported to WHO from routine surveillance and periodic surveys from the period from 2003 to 2017 and found that Isoniazid is the most critical drug used in the treatment of active TB, and also used for the preventive treatment of TB [42]. Isoniazid mono-resistance is the most common form of DR-TB in the world [39,43,44]. INH mono-resistance escalates the chances of poor treatment outcomes and a progression to MDR-TB [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in different settings indicated that isoniazid mono-resistant TB is a problem in different countries [4][5][6][7][8]. The incidence of isoniazid mono-resistant TB is increasing and it is higher than RR-TB globally [9].…”
Section: Introductionmentioning
confidence: 99%